O efeito das falas patológicas: questões relativas à avaliação de linguagem nos casos de autismo e psicose infantil - Barbosa, Caroline Lopes (2011)
Studies about the speech of patients with autism and psychosis in children that were attended on the speech therapy are studied little, that means, there are not many works that focuses on the speech of this children. In this work is necessary to understand the way the language of this patients works, in order to address these clinical issues, such as the evaluation of the speech and the therapy on the attendance of this cases, which have make the speech therapist come closer to areas such as Psychoanalysis, the Medicine, and also the Linguistics, once the description of this cases indicates language disorders with relevant manifestation for a diagnosis. In this sense, I place in to question the way the speech therapist takes care of the autism and psychosis in children, to understand another view of analyses that could take into consideration the relationship between the subject and the language, in view of the language and the treatment processes. I have put into place a critical discussion on the matters related the autism and psychosis in children cases and it repercussion to Psychoanalyses and how they were understand by the Medicine. In view of that, I have came close to the Reserch Group named Language acquisition, language pathology and language clinic , under coordination of the Professors and Doctors Maria Francisca Lier-De Vitto and Lucia Arantes, on (LAEL/PUCSP), in which is possible to think in imbrications among subjective structures and language structuring, as well in the relationship among the subject and the language